Resiliensi Psikologis pada Remaja dari Keluarga Penyandang Skizofrenia - Agustina Rahmah; Andi Wahyu Irawan (Cetta: Jurnal Ilmu Pendidikan, 2026)
Schizophrenia is a mental disorder that affects the way of thinking, emotions, behavior, and interpreting reality, thus hindering daily activities. This study aims to understand and analyze the process of psychological resilience in adolescents living with family members with schizophrenia, how they are able to adapt healthily, manage emotional stress, and maintain psychological health amidst challenging family conditions. This study used a qualitative method with a case study approach. Data collection techniques included interviews, observation, and documentation. Participants were selected using purposive sampling. The data analysis technique used was interactive analysis, consisting of data collection, data reduction, data presentation, and conclusion drawing. The results showed that adolescents with family members with schizophrenia have well-developed psychological resilience abilities in aspects of self-regulation, positive thinking patterns, and cognitive and social abilities. This study is expected to provide an overview of how the process of increasing psychological resilience in adolescents living with families with schizophrenia and providing support to people who have similar experiences. The researchers recommend that further research can expand the number of participants to make the results more representative.